Family center maternity care education for pregnant women through the approachin efforts to prevent stunting: a quasi-experimental - Desiyanti, Irne Wida; Ardiningtyas, Lisa (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Background: Stunting in children is a health problem that has a great influence on their physical and mental development. In Indonesia, one of the causes of high stunting rates is the low health awareness of pregnant women, especially those who marry at a young age. Family factors have a significant influence on the success of stunting prevention, but family-based approaches are still rarely applied in pregnant women’s health education programs. Purpose: This study aims to develop and evaluate the effectiveness of the Family Centered Maternity Care (FCMC)-based education approach in increasing knowledge and efforts to prevent stunting in pregnant women in Kolongan, North Minahasa. Methods: This study uses a quasi-experimental design with a pretest-posttest approach. The research sample consisted of 20 pregnant women who met the inclusion criteria. Data were collected through stunting knowledge questionnaires and stunting prevention efforts questionnaires, which were measured before and after FCMC interventions. Data analysis was carried out using the Wilcoxon test with a significance value of p<0.05. Results: The results of the study showed a significant increase in the level of knowledge and stunting prevention efforts among pregnant women after being given FCMC-based educational interventions. Before the intervention, only 25% of participants had high knowledge about stunting, but after that it increased to 75%. Stunting prevention efforts have also increased from 40% to 80%. The Wilcoxon test showed that this change was statistically significant (p = 0.033). Conclusion: The FCMC-based education approach has proven to be effective in increasing knowledge and efforts to prevent stunting in pregnant women. This education can be a reliable method in increasing awareness and preventive measures of pregnant women against the risk of stunting in their children.